Penggunaan Asam Hialuronat untuk Penatalaksanaan Black Triangle - Tandjaja, Cynthia; Astuti, luki (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Introduction: The absence of interdental papilla between two teeth is called Black Triangle. It will affect the patient’s aesthethic aspect. Giving hyaluronic acid’s injection can be one of the treatment to heal the condition. Literature Review: There’s few factors that influence the absence of interdental papilla such as the length from bone crest to the contact point between two teeth. The thickness and the periodontal biotype can also effect the condition. Hyaluronic acid is one of the most biocompatible material with human body. The concentration of hyaluronic acid that got affected by the molecular weight also have their own benefit. Discussion : Hyaluronic acid will bind with water, and become the receptor of mediated cell division and will increase the tubulin concentration that is responsible to increase the proliferation of fibroblast and also the synthesis of collagen. Conclusion: Hyaluronic acid can be one of the option to heal black triangle.